House X at Kommos : a Minoan mansion near the sea. - Jeremy, Rutter (Prehistory monographs ;, 2017)
This volume presents the Late Bronze Age pottery from in and around House X, a large Minoan house at Kommos situated not far from the sea in South-Central Crete. Rutter's contribution complements the publication of the architecture, stratigraphy, and small finds in Part 1 (Shaw and Shaw, eds., 2012). The Kommos series is now completed by the two-volume publication on House X.